2021
DOI: 10.1021/jacs.1c03988
|View full text |Cite
|
Sign up to set email alerts
|

Harzianic Acid from Trichoderma afroharzianum Is a Natural Product Inhibitor of Acetohydroxyacid Synthase

Abstract: Acetohydroxyacid synthase (AHAS) is the first enzyme in the branched-chain amino acid biosynthetic pathway and is a validated target for herbicide and fungicide development. Here we report harzianic acid (HA, 1) produced by the biocontrol fungus Trichoderma afroharzianum t-22 (Tht22) as a natural product inhibitor of AHAS. The biosynthetic pathway of HA was elucidated with heterologous reconstitution. Guided by a putative self-resistance enzyme in the genome, HA was biochemically demonstrated to be a selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 64 publications
1
36
0
Order By: Relevance
“…Literature review revealed that the substance corresponding to this molecular formula might be harzianic acid (HA) [42,[47][48][49][50]. In addition, the UV absorption of peak 1 with λ max 238 and 358 nm (Figure S1) was similar to those found for HA in multiple reports [42,[50][51][52]. The identity of HA was confirmed using LC/MS/MS spectra in the positive ionization mode which showed distinct product ions (Figure 1c 1 ,c 2 ) corresponding to the already predicted mass spectra of HA [47,53].…”
Section: Identification Of the Chemical Structures Of Sms From Tricho...supporting
confidence: 63%
“…Literature review revealed that the substance corresponding to this molecular formula might be harzianic acid (HA) [42,[47][48][49][50]. In addition, the UV absorption of peak 1 with λ max 238 and 358 nm (Figure S1) was similar to those found for HA in multiple reports [42,[50][51][52]. The identity of HA was confirmed using LC/MS/MS spectra in the positive ionization mode which showed distinct product ions (Figure 1c 1 ,c 2 ) corresponding to the already predicted mass spectra of HA [47,53].…”
Section: Identification Of the Chemical Structures Of Sms From Tricho...supporting
confidence: 63%
“…It is therefore suggested that future design efforts should be concentrated on inhibitors that avoid entering that space. In this regard, it is worth pointing out the mode of binding of the recently isolated natural product inhibitor of AHAS, harzianic acid 28 . This compound not only takes a conformation avoiding the region where the oxidative side-reaction occurs, but also makes interactions within a region of the catalytic pocket that has not been used by any of the existing commercial herbicides.…”
Section: Discussionmentioning
confidence: 99%
“…harzianum. , The biosynthetic pathway of HA was newly elucidated in T. afroharzianum, and HA was biochemically characterized to be a selective inhibitor of fungal acetohydroxyacid synthase (AHAS), which was a validated target for fungicide development . There is no obvious difference between the expression levels of WT and KO- ThpacC concerning the biosynthetic core genes for HA production, which supported that HA production could be ThpacC-independent and pH-dependent.…”
Section: Resultsmentioning
confidence: 89%